Respostas
respondido por:
27
( x + 2 ) . ( x - 16 ) + ( x + 7 )² = 89
x² - 16x + 2x - 32 + ( x + 7 ) . ( x + 7 ) = 89
x² - 14x - 32 + x² + 7x + 7x + 49 = 89
2x² + 17 = 89
2x² = 72
x² = 72 / 2
x² = 36
x = √36
x = 6
x² - 16x + 2x - 32 + ( x + 7 ) . ( x + 7 ) = 89
x² - 14x - 32 + x² + 7x + 7x + 49 = 89
2x² + 17 = 89
2x² = 72
x² = 72 / 2
x² = 36
x = √36
x = 6
respondido por:
8
(x+2)(x-16) + (x+7)² = 89
(x+2)(x-16) + (x+7)(x+7) = 89
(x²-16x+2x-32) + (x²+7x+7x+49) = 89
x²-14x-32+x²+14x+49=89
2x²+17=89
2x²=89-17
2x² = 72
x² = 72/2
x²= 36
x = √36
x = 6
(x+2)(x-16) + (x+7)(x+7) = 89
(x²-16x+2x-32) + (x²+7x+7x+49) = 89
x²-14x-32+x²+14x+49=89
2x²+17=89
2x²=89-17
2x² = 72
x² = 72/2
x²= 36
x = √36
x = 6
Perguntas similares
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás